APPLICATION OF LANDSAT-8 OPERATIONAL LAND IMAGER AND SHUTTLE RADAR TOPOGRAPHY MISSION-DIGITAL ELEVATION MODEL IN THE STUDY OF IKARA AND ITS ENVIRONS, NORTHWESTERN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
Images of the earth’s surface captured by radiometric detectors on air-borne (satellite) sensors were employed in geologic reconnaissance survey. They were used to study rock units, pattern and trends of geologic structures on the surface in 2D. Multispectral resolution Landsat-8 Operational Land Imager (Landsat-8 OLI), have nine spectral band with spatial resolution of 30 m (bands 1 to 7, and 9) and 15 m for band 8. The aim of this research is to discriminate lithological units/complexes and delineate fractures (lineaments), hence, only bands 2 to 7 were used for this study. This technique was used to discriminate existing lithological units and identify major and minor extensive geologic structures within the study area. These selected bands were selected, grouped and combined (Band Combination (BC)) and processed for interpretation using applicable Software Packages. Hence, for each procedure and maximum clarity in the output of results, three bands were combined for each analytical process. Bands 4,3,2; 6,5,4; 7,5,3 were combined for Natural Colour Composite (NCC), False Colour Composite (FCC) and Principle Component Analysis (PCA) respectively. The results revealed two distinct lithological Complexes due to their similarities in appearance and differences in mineralogical compositions. SRTM-DEM was used to highlight the topography showing the lowest relief at the northeast and the highest relief at the south east. More so, elongated ridges of intermediate-high reliefs were exposed at the southern part of the study area trending NW-SE. A lineament map and Rose plot shows dominant trend of fractures to be NNW-SSE, NW-SE, N-S,
Keywords: Landsat-8 OLI, Band Composites, Principal Component Analysis, SRTM-DEM, Lineaments